ECONOMIC-ORGANISATIONAL ASPECTS OF MUSIC SCHOOL MANAGEMENT BY A LOCAL AUTHORITY UNIT - Małecki, Tomasz (Review of European and Comparative Law, 2018)
The article presents the selected economic-organisational aspects of music school management by a local authority unit. The author focuses on the issues related to the costs of upkeep of a music school, the opportunities of obtaining additional funds and management control by the headmaster. The thesis of the article is the statement that the headmaster establishing an association or a foundation, which will support the school financially, is a solution for the insufficiency of the funds received for its functioning. In the light of the binding regulations, school is a public finance budget unit, therefore, all the funds obtained by school, e.g. from letting a concert hall, are the property of the managing body. That is why the headmaster, when searching for additional funds, is forced to reach for unconventional solutions in the forms of establishing an association or a foundation.